IMPLEMENTASI PENILAIAN AUTENTIK KURIKULUM 2013 MATA PELAJARAN EKONOMI SMAN 1 MOJOSARI MOJOKERTO - Elok Gita Yuliastuti (Jurusan Ekonomi Pembangunan Fakultas Ekonomi Universitas Negeri Malang, 2017)
This research is aiming to know authentic assessment was essential toknow the success of the learning process and results. authenticassessment is a form of assessment that requires students to show attitude, using the knowledge and skills gained from learning in the conduct ofthe actual situation. to know how to design an authentic assessment oneconomic studies, implementation of authentic assessment on economicstudies as well as factors of curriculum 2013 constraints authenticassessment on economic studies in SMAN 1 Mojosari, Mojokerto. Theeconomy studies in SMAN 1 Mojosari has been implementing authenticassessment based curriculum 2013, so to be seen whether theimplementation of authentic assessment conducted in SMAN 1 Mojosarihave maximum and curriculum assessment in accordance with theguidelines of 2013. DOI: https://dx.doi.org/10.17977/UM014v10i12017p075